Handbook of glass properties - Bansal, Narottam P. (Academic Press, 1986)
This volume is a compilation of data on the properties of glasses. The authors have critically examined and correlated the most reliable data on the properties of multicomponent commercial silicate glasses, vitreous silica, and binary and ternary laboratory glasses. Thermodynamic, thermal, mechanical, electrical, and transport properties are covered. Measurement methods and appropriate theories are also discussed.
Keywords: Glass -- Handbooks, manuals, etc.; elektronické knihy; electronic books